Improving The Capacity of Learning Financial Literacy and Environmental Aspects in Early Childhood: Meningkatkan Kapasitas Pembelajaran Literasi Keuangan dan Aspek Lingkungan pada Anak Usia Dini - Yuliarini, Sarah; Purwitasari, Fadilla; Popiyanto, Yudha (Universitas Haji Sumatera Utara, 2025)
Holistic Integrative (HI) for the implementation of IKM at the kindergarten/early childhood education/playgroup level and equivalent, which focuses on the development of student learning outcomes encompassing competencies (literacy and numeracy) and character, will still be mandatory to implement by 2024 at the latest. The PKM program will provide opportunities for lecturers in the fifth IKU, namely the Work Results of Lecturers Used by the Community, by designing experiential learning methods using supporting Educational Play Tools (APE) as learning media to be developed to support students' financial literacy skills in management. Financial literacy and aspects of the physical and non-physical/social environment are important components of life. Both interact with each other in daily life, especially regarding the effectiveness and efficiency of energy use, which impacts the family's financial allocation. This helps accelerate the transformation from the 2013 Curriculum and/or the 2013 Emergency Curriculum to the IKM.